A Corpus-Based Study on Reporting Verbs Used in Tesol Research Articles by Native and Non-Native Writers - Tham, Duong My; Nhi, Tran Phuong (VNU Journal of Foreign Studies; Vol 37 No 3DO - 10.25073/2525-2445/vnufs.4729, 2021)
This corpus-based research aimed to compare the use of reporting verbs in TESOL research articles between non-native and native English writers. Two corpora including 30 for the non-native corpus and 30 for the native corpus were constructed for analysis. The data in the form of plain text were processed via AntConc software version 3.5.7. The findings indicated significant differences in terms of frequency, function, and position between the two corpora. Specifically, more reporting verbs were found in the non-native corpus than in the native corpus. Of four verb groups of Argue, Find, Show, and Think, Argue group was the top priority used in TESOL research articles by both non-native and native English authors. The results of the functional and positional analysis in both the corpora also showed that two most common functions of reporting verbs were (1) presentation and (2) evaluation and examination, and most of the observed reporting verbs were in neutral position.